2018
DOI: 10.18052/www.scipress.com/ilns.69.1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Maize Varieties to Salt Stress in Relation to Germination and Seedling Growth

Abstract: A pot experiment was carried out at the Laboratory of Department of Agronomy, Hajee Mohamad Danesh Science and Technology University (HSTU), Bangladesh during 2016 to evaluate the response of maize varieties at germination and seedling growth stages under salt stress. The seeds of the BARI (Bangladesh Agricultural Research Institute) developed four maize varietiesviz.Barnali, Khoi Vutta, Mohor and BARI Maize 5 were placed in plastic pots (each of 25 cm length and 12 cm width) on sand bed irrigated with tap wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Higher K + /Na + ratio is a key factor that helps the salt-tolerant genotypes to perform well under salinity by regulating enzymes activation, osmoregulation and regulating cell turgor pressure with enhanced photosynthetic activity (Abbasi et al, 2012). Similar results were reported in maize by Hassan et al (2018). The salt sensitivity of maize hybrids 8711 and 8441 was also because of their inability in retaining high K + concentration in the cell sap that resulted in lower K + /Na + ratio.…”
Section: Resultssupporting
confidence: 82%
“…Higher K + /Na + ratio is a key factor that helps the salt-tolerant genotypes to perform well under salinity by regulating enzymes activation, osmoregulation and regulating cell turgor pressure with enhanced photosynthetic activity (Abbasi et al, 2012). Similar results were reported in maize by Hassan et al (2018). The salt sensitivity of maize hybrids 8711 and 8441 was also because of their inability in retaining high K + concentration in the cell sap that resulted in lower K + /Na + ratio.…”
Section: Resultssupporting
confidence: 82%
“…27 These effects observed with the eggplant plants from control and non-induced pre-treatments in the present study. An increased salt concentration causes a low water balance in tissue water, 28,29 and reason for this reduction in fresh biomass of eggplants under non-induced and control treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Qu et al (2012), who observed that salinity accelerated leaf abscission along with reducing inter-nodal development which resulted in stunted shoot growth. It was inferred that reduction in root and shoot growth might be attributed to sensitivity of cultivars to slight increment in salinity level in the growth medium (Hassan et al, 2018).…”
Section: Root Length (Cm)mentioning
confidence: 99%
“…Globally, soil salinity has emerged as the leading challenge to modern farming systems which reduces crops yield by damaging the different cellular functions of plants. Gradually, accumulation of salt in upper soil horizons leads to destruction of soil structure and texture (Hassan et al, 2018). Among abiotic stresses, soil salinity has posed a serious threat all over the world to global food security by affecting over 7% of the land area across the globe (Hasan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%